The Impact of Teacher Immediacy and Humor on Undergraduate Student Classroom Engagement: Evidence from Pakistan - Hussain, Tariq; Ali, Zunaira Hakim; Naz, Anjum (Journal of Development and Social Sciences, 2024)
This study investigates the impact of teacher immediacy and humor on undergraduate student engagement in Pakistani higher education. The primary goal is to identify how these behaviors influence engagement and to analyze gender and institutional differences in their effects. Through verbal and non-verbal communication, teacher immediacy lowers psychological distance and increases student engagement and motivation. Humor fosters an engaging learning environment that fosters creativity and enjoy, which is a great way to balance immediacy. Using a quantitative correlation methodology, 456 undergraduate students from 9 universities (4 public, 5 private) in Lahore were surveyed. A self-developed questionnaire that assessed student engagement, humor, and teacher immediacy was used to gather data. Relationships and predictive impacts were evaluated by statistical studies, such as regression and Pearson correlations. The findings revealed a strong positive correlation between immediacy and engagement (r = 0.538, p < 0.001) and a moderate correlation between humor and engagement (r = 0.462, p < 0.001). Regression analysis showed immediacy as a stronger predictor of engagement (β = 0.417) than humor (β = 0.287). Male and private university students demonstrated higher engagement levels. Teachers should be trained to use immediacy and humor effectively, fostering engaging and dynamic classrooms. Gender-sensitive approaches are essential to ensure balanced engagement for all students. Public universities should adopt interactive teaching methods and enhance student-teacher interaction to boost engagement. Encouraging active participation through group work and discussions can further create an inclusive learning environment.